Optimization of carbon dioxide supply in raceway reactors: Influence of carbon dioxide molar fraction and gas flow rate. (July 2016) - Duarte-Santos, T.; Mendoza-Martín, J.L.; Acién Fernández, F.G.; Molina, E.; Vieira-Costa, J.A.; Heaven, S.
Highlights: Gases containing different CO2 molar fraction can be used to control pH in raceway. CO2 efficiency is maximal when minimizing the gas flow rate and molar fraction. In raceways major CO2 losses take place in sump, next in channels and paddlewheel. Optimal system allows achieving 85% conversion of supplied CO2 into biomass. Abstract: Influence of CO2 composition and gas flow rate to control pH in a pilot-scale raceway producing Scenedesmus sp. was studied. Light and temperature determined the biomass productivity whereas neither the CO2 molar fraction nor the gas flow rate used influenced it; because pH was always controlled and carbon limitation did not take place. The CO2 molar fraction and the gas flow rate influenced carbon loss in the system. At low CO2 molar fraction (2–6%) or gas flow rate (75–100 l·min −1 ) the carbon efficiency in the sump was higher than 95%, 85% of the injected carbon being transformed into biomass. Conversely, at high CO2 molar fraction (14%) or gas flow rate (150 l·min −1 ) the carbon efficiency in the sump was lower than 67%, 32% of the carbon being fixed as biomass. Analysis here reported allows the pH control to be optimized and production costs to be reduced by optimizing CO2 efficiency.